Implikasi Postmodernisme Dalam Masyarakat Kontemporer (Analisis Paradigma Pemikiran Tokoh Jean Francois Lyotard) - Erlina, Erlina; Helmi Syaifuddin (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2023)
This article aims to investigate the implications of postmodernism in contemporary society by analyzing the paradigm of thought of the figure Jean-François Lyotard. Lyotard is known as one of the leading thinkers in postmodern thought, and this research aims to understand how his idea of skepticism towards grand narratives influences and permeates the structures of power, knowledge, and language in the context of contemporary society. This study uses a qualitative approach with a focus on the analysis of key texts by Jean-François Lyotard, especially "The Postmodern Condition: A Report on Knowledge." Analysis is performed to identify key concepts such as grand narratives, language games, and changes in knowledge structure. In addition, literature studies on the application of these concepts in the context of contemporary society are also involved to support research findings. The research findings suggest that Lyotard's postmodern views have significant implications in contemporary society. Skepticism of grand narratives creates space for narrative plurality, uncertainty of knowledge, and diverse language games. These implications affect power structures by challenging central authority and paving the way for a diversity of values and views. In addition, Lyotard's concepts also had an impact on changes in the way society understood and conveyed knowledge.